THE EFFECT OF PAIRED TRAINING ON THE DOWN PASSING SKILL OF VOLLEYBALL IN MADRASA ALIYAH UINSU LABORATORY 2019 - Ahmad Al Munawar; Fajar Mugo Raharjo (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to determine the effect of pairing passing exercises on the results of passing skills under volleyball games. The research method used is an experimental method. The population in this study were all students who participated in volleyball extracurricular activities in the 2018/2019 school year, amounting to 27 people, while the samples were taken with a proposive sampling technique so that a sample of 12 people were obtained. through paired training the tcount is 2.04 and the table is 2.02 with Î± = 0.05 (tcount> t table) means that Ho is rejected and Ha is accepted. So, in other words, there is a significant influence of paired training on the passing skills of volleyball on Volleyball Extracurricular at Madrasah Aliyah, UIN SU Laboratory, 2019 Medan.